Natural Lighting in Historic Houses during Times of Pandemic. The Case of Housing in the Mediterranean Climate - Muñoz-González, Carmen María; Ruiz-Jaramillo, Jonathan; Cuerdo-Vilches, Teresa; Joyanes Díaz, María Dolores; Montiel-Vega, Laura; Cano Martos, Victor; Navas Martín, Miguel Ángel (MDPI, 2021)
The pandemic generated by the SARS-CoV-2 virus has led to a forced increase in the number of hours spent at home. In many cases, the lockdown situations, both in social and work terms, have meant that homes have suddenly also become workplaces. Based on all the indicators, this new relational scenario in the labor market displays a clear upward trend and is far from being a temporary situation. It is known that sunlight affects people’s circadian rhythm and that its reduction and even absence during this period of isolation has had a psychological impact on the population. This makes it necessary to reconsider the regulations applied in homes, in order to guarantee their habitability, given their recent widespread use as offices, as well as domestic spaces. In historic centers, the comprehensive renovations being carried out include improvements in energy efficiency and thermal comfort, which play a fundamental role. However, the energy consumption linked to artificial lighting and the quality of this lighting itself have remained in the background, as improvement strategies consist mainly in the replacement of incandescent or fluorescent lamps with LED lamps. Prior to the pandemic, the electric consumption of lighting systems accounted for 10–15% of the total, a figure which increased to 40–50% during the lockdown period. Aiming to improve people’s well-being while reducing energy expenditure on lighting, this article presents a quantitative approach to improving the levels of natural lighting in residential heritage buildings located in historic centers. According to data obtained from previous surveys of a sector of the population, homes built prior to 1950 were characterized by good natural lighting conditions and a very low incidence of health issues among occupants compared to contemporary homes.
Keywords: Viviendas; Iluminación natural; Cambio climático; Daylighting; Residential heritage; COVID-19; Lockdown; Climate change; Simulation; Survey; Circadian rhythm